2004
DOI: 10.1074/jbc.m312782200
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol-independent Interactions with CD47 Enhance αvβ3 Avidity

Abstract: Expression in OV10 cells of either wild-type CD47 or its extracellular IgV domain linked to a glycosylphosphatidylinositol anchor-(IgV-GPI) enhanced ligand-induced ␣ v ␤ 3 activation as detected by the binding of LIBS1 and LIBS6 mAbs. The amplitude of LIBS binding was greater with both CD47 and IgV-GPI expression, indicating an increase in the population of "activable" integrin molecules. Expression of either CD47 species also increased ␣ v ␤ 3 -mediated adhesion to vitronectin, and to surfaces coated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 44 publications
3
44
0
Order By: Relevance
“…The increase in cyclic AMP resulted probably from the activation of adenylyl cyclase, given that our measurements were performed in the presence of the phosphodiesterase inhibitor 3-isobutyl-1-methylxanthine. Furthermore, there have been reports that ␣ v ␤ 3 integrin and integrin-associated protein (CD47) may combine to form a functional seven-transmembrane complex, which associates with G i protein and,once activated, decreases cyclic AMP (39). Thus, ␣ v ␤ 3 -CD47-G i complexes could be involved in the control of adenylyl cyclase activity by ␣ v ␤ 3 engagement/disengagement.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in cyclic AMP resulted probably from the activation of adenylyl cyclase, given that our measurements were performed in the presence of the phosphodiesterase inhibitor 3-isobutyl-1-methylxanthine. Furthermore, there have been reports that ␣ v ␤ 3 integrin and integrin-associated protein (CD47) may combine to form a functional seven-transmembrane complex, which associates with G i protein and,once activated, decreases cyclic AMP (39). Thus, ␣ v ␤ 3 -CD47-G i complexes could be involved in the control of adenylyl cyclase activity by ␣ v ␤ 3 engagement/disengagement.…”
Section: Discussionmentioning
confidence: 99%
“…This compartment is believed to consist of membrane microdomains, denominated lipid rafts, that are enriched in cholesterol and glycosphingolipids, implicated in several processes, including signal transduction, endocytosis, membrane trafficking, cytoskeletal reorganization and pathogen entry (Munro, 2003;Pike, 2004). α V β 3 integrin may be accumulated in rafts (Triantafilou and Triantafilou, 2003), and its ligand-induced activation is enhanced by glycosyl phosphatidylinositol anchor (McDonald et al, 2004). Lipid raft integrity is required for receptor-mediated actin cytoskeleton reorganization and PKCα translocation (Becart et al, 2003) and the raft fraction is assumed to be important for the Ca 2+ signalling and the Ca 2+ -dependent association of classical PKC to these microdomains (Orito et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have indicated that CD47 and LYN affect the integrin activation signal. 35 The CD47/SIRPa axis negatively regulates human immunity by inhibiting MDSCs maturation. 36 Interestingly, Western blot analysis indicated that the CD47/ SIRPa axis was almost completely inhibited by dasatinib treatment (Fig.…”
Section: Tumor Immunology and Microenvironmentmentioning
confidence: 99%